Maniac Magee : a novel - Spinelli, Jerry (New York : Little, Brown and Co., 2004)
After his parents die, Jeffrey Lionel Magee's life becomes legendary, as he accomplishes athletic and other feats which awe his contemporaries.
820
Newbery Medal, 1991.
Keywords: Courage -- Fiction; City life -- Fiction